Cytoplasmic Male Sterility Incidence in Potato Breeding Populations with Late Blight Resistance and Identification of Breeding Lines with a Potential Fertility Restorer Mechanism - Santayana, M.; Aponte, M.; Kante, M.; Eyzaguirre, R.; Gastelo, M.; Lindqvist-Kreuze, H. (MDPI, 2022)
Cytoplasmic male sterility (CMS) in potato is a common reproductive issue in late blight breeding programs since resistant sources usually have a wild cytoplasmic background (W or D). Nevertheless, in each breeding cycle male fertile lines have been observed within D- and T-type cytoplasms, indicating the presence of a fertility restorer (Rf) mechanism. Identifying sources of Rf and complete male sterility to implement a CMS–Rf system in potato is important since hybrid breeding is a feasible breeding strategy for potato. The objective of this study was to identify male fertile breeding lines and potential Rf candidate lines in the CIP late blight breeding pipeline. We characterized male fertility/sterility-related traits on 142 breeding lines of known cytoplasmic type. We found that pollen viability is not a reliable estimate of male sterility in diverse backgrounds. Breeding lines of the T-type cytoplasmic group had higher levels of male fertility than breeding lines of the D-type cytoplasmic group. With the help of pedigree records, reproductive traits evaluations and test crosses with female clones of diverse background, we identified four male parental lines segregating for Rf and three female parental lines that generated 100% male sterile progeny. These identified lines and generated test cross progenies will be valuable to develop validation populations for mitochondrial or nuclear markers for the CMS trait and for dihaploid generation of Rf+ lines that can be later employed in diploid hybrid breeding.